Giant hepatic hemangioma in the fetus: case reports and updated review of the literature. (3rd August 2021) - Sepulveda, Waldo; Sepulveda, Francisco; Corral, Edgardo; Gutierrez, Jorge
Abstract: Objectives: To describe three cases of giant fetal hepatic hemangioma detected by prenatal ultrasound in the third trimester of pregnancy and further confirmed by fetal magnetic resonance imaging (MRI). An updated review of the literature was also carried out. Results: In one case, there was an unexpected intrauterine demise at 35 weeks. The other two women delivered liveborn infants at term. The first of these two neonates had a stormy neonatal course and underwent endovascular embolization with limited clinical success. The infant presented multiple medical complications and was discharged home at five months of age. The second infant had an uneventful postnatal course. Subsequent follow-up scans showed progressive shrinkage of the lesion with no associated complications. A review of the English literature revealed a total of 42 cases prenatally diagnosed by ultrasound. The most relevant clinical and ultrasound findings are presented and the diverse perinatal outcomes related to this condition are discussed. Conclusions: Fetal hepatic hemangiomas are exceedingly rare vascular tumors; however, they can be associated with several life-threatening conditions. They are usually detected by ultrasound, either incidentally or in the context of nonimmune hydrops secondary to high-output cardiac failure. Our review documents the increasing role of fetal MRI in the prenatal diagnosis and management of these cases. However, the improvement in prenatal diagnostic imaging techniques has not been associated with a better perinatal prognosis in the reported cases.